Wellens's Syndrome, Kenali karena setara dengan stemi: laporan kasus - FIHA; FASCC; FAPSC; Kristivani Br Ginting; Andika Sitepu (Medistra Medical Journal (MMJ), 2024)
Acute coronary syndrome (ACS) is one of the leading causes of acute chest pain, requiring emergency care and eventual hospitalization. Wellens’ syndrome is one such example, which in ACS patients is a catastrophic event often accompanied by extensive anterior myocardial infarction and high mortality rates. Wellens’ syndrome is a pattern of T-wave changes seen in the anterior (V2-V3) leads on critical stenosis of the left anterior descending (LAD) coronary artery. We reported a 65-year-old man admitted to our emergency facility because of intermittent chest pain that had been experienced for the past 2 days. An initial ECG performed in the emergency room while pain free showed sinus rhythm with biphasic T waves in V2–4 which is typical of Wellen's Syndrome. Chest x-ray shows cardiomegaly. Cardiac enzyme examination showed an increase in CKMB and Troponin T levels of 18.40 U/L and 560 ng/L respectively. The echocardiography (ECHO) demonstrated a hypokinesis of the anteroseptal with left ventricular ejection fraction (LVEF) of 47 %. Cardiac catheterization showed total occlusion in the mid-LAD and other coronary arteries had non-significant lesions. He then underwent balloon angioplasty and placement of a stent in the proximal and mid LAD with a good result. Wellen’s syndrome often represents a pre-infarction state of myocardial infarction. Early recognition of these ECG features is crucial to identify these high-risk clients, and the definitive evaluation and treatment is cardiac catheterization with intervention to relieve the LAD obstruction.